Types of Environmental Enrichments Offered for Cats and their Association with Housing Features and Cat Personality - da Silva Gonçalves, Luana; de Souza Machado, Daiana; de Castro Travnik, Isadora; Sant’ Anna, Aline Cristina [UNESP] (Taylor & Francis, 2025)
Environmental enrichment designed in accordance with the cats’ individuality and household characteristics is one of the most effective and widely used tools to enhance feline welfare. This study aimed to evaluate the types of environmental enrichments provided by cat guardians and their associations with housing features and cat personality. An online questionnaire was developed including questions about types of enrichment provided, housing features (indoor vs. outdoor, house vs. apartment), and a scale with 18 personality traits. A total of 3,083 responses were collected. Most of the guardians declared to provide environmental enrichment items for their cats. The items most offered were play interaction (77.4%), access to a balcony and/or window with a protective net (72.7%), places to hide (54.5%), and toys (46.0%). The items with lower frequencies were water fountains (34.5%), self-groomers (11.3%), outdoor walks on a leash (6.5%), and food puzzles (3.5%). The choice of enrichment items was more related to housing features than to the cat’s personality. Enrichment provision was more associated with indoor housing and cats living in apartments than with cats living outdoors and in houses.
Keywords: Behavior; domestic cats; temperament; welfare